Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

3(x-6)^4+11=15 solve for x

Sagot :

Answer:

x = 7.07 or 4.925

Step-by-step explanation:

3(x-6)^4+11=15

3(x-6)^4=15-11

(x-6)^4=4/3

x-6 = +[tex]\sqrt[4]{4/3}[/tex] or -[tex]\sqrt[4]{4/3}[/tex]

x= +[tex]\sqrt[4]{4/3}[/tex] +6 or -[tex]\sqrt[4]{4/3}[/tex]  +6

x = 7.07 or 4.925